2023
DOI: 10.21203/rs.3.rs-3057278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the effect of migration status on family planning utilisation in Malawi. Evidence from 2019/20 Malawi Multiple Indicator Cluster Survey

Abstract: Background: Family planning (FP) is known to bring multiple benefits to people both individually and collectively. Individually, FP has been associated with reduction in risk of unintended pregnancy which also correlates well with low child mortality rates. Child mortality rates in women with child spacing of less than two years are reported to be 45% higher than their counterparts. Several factors that predict FP utilisation have been investigated but there is limited literature on the effect of migration sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Prevalence of modern contraceptive use in SSA ranged from 5% in Chad to 70% in South Africa among parenting adolescents (22). In Malawi, the contraceptive prevalence rate among adolescents is still low ranging from 9% for single nulliparous adolescents to 45% among parenting married adolescents (23)(24)(25). A study on school going adolescent preferences and views on family planning in Malawi showed that adolescent girls had limited knowledge on availability of modern contraceptive methods and were hesitant to use family planning methods due to stigma associated with using modern contraception among unmarried adolescents (26).…”
mentioning
confidence: 99%
“…Prevalence of modern contraceptive use in SSA ranged from 5% in Chad to 70% in South Africa among parenting adolescents (22). In Malawi, the contraceptive prevalence rate among adolescents is still low ranging from 9% for single nulliparous adolescents to 45% among parenting married adolescents (23)(24)(25). A study on school going adolescent preferences and views on family planning in Malawi showed that adolescent girls had limited knowledge on availability of modern contraceptive methods and were hesitant to use family planning methods due to stigma associated with using modern contraception among unmarried adolescents (26).…”
mentioning
confidence: 99%